Republic of Madagascar : Fifth Review Under the Extended Credit Facility Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Republic of Madagascar. (IMF Staff Country Reports; Country Report ;, 2019)
Despite some electoral cycle-related uncertainties-the preparation and holding of the Presidential election in December 2018 and Parliamentary elections in May 2019-economic developments remained favorable in 2018 and the first months of 2019. Macroeconomic slippages were limited, with spending strictly contained within budget limits. The stable functioning of public institutions allowed for continued implementation of the economic reform program.